Kompetensi Dakwah Dan Praktek Safari Romadlon Santri Darussalam Sumbersari Kencong Kepung Kediri - Rohmad (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
This study concerns the competence of da'wah and Romadlon safari practices which are specifically directed at santri in the Islamic Boarding School of Sumbersari Kencong Kepung, Kediri Regency relating to the plunge of students studying in the community for nasyrul ilmi waddin related to da'wah which is manifested in the form of safari Romadlon. This type of research approach is qualitative phenomenological, with a case study design. Data collection is done by in-depth interview techniques, observation, and study documentation. While the data analysis technique, researchers used an interactive analysis model that contained four interrelated components, namely: data collection, data simplification, data exposure, withdrawal and submission of conclusions. Finally, this study managed to obtain findings in accordance with the problem questions which in general can be concluded as follows: 1). Da'wah planning implemented at Darussalam Sumbersari Islamic boarding school in general can be said to be good which includes training, screening of all Romadlon safari participants so that safari activities can go well, 2). Romadlon safari practices by recording areas that will be occupied by the students went well, 3). Santri who was deployed assisted by the Romadlon safari committee was felt to be able to overcome the existing problems both internally and externally.